IMMUNE THROMBOCYTOPENIC PURPURA (ITP) IN CHILDREN AND ADULTS: INCIDENCE AND BONE MARROW ASPIRATION FINDINGS IN HIWA HOSPITAL, SULAIMANI CITY - M.Salih, Kurdo Nawzad; Abdullah, Dana Ahmed (Journal of Sulaimani Medical College, 2024)
Background Immune thrombocytopenic purpura is an autoimmune disease mainly affecting children. Objectives This study aimed to find out the incidence of Immune thrombocytopenic purpura and whether the peripheral platelet destruction affected bone marrow megakaryocytes. Patients and Methods This retrospective observational study was performed on 108 confirmed patients admitted to Hiwa Hospital, Sulaimaniyah, Iraq, from January 01, 2018, to December 31, 2021. Socio-demographic features, family history, presentations, and laboratory/ultrasonography findings were recorded. Results The incidence of Immune thrombocytopenic purpura in patients aged <18 years, ≥18 years, and >60 years were 5.9, 4.4, and 19.5 per 100,000 persons, respectively. The mean age of patients was 27.7±24.5 years, in which 41.7% were males and 58.3% were females, with the male/female ratio for <18, ≥18, and > 60 of 1.4:1, 0.34:1, and 0.58:1, respectively. Among patients; 17.6% had secondary Immune thrombocytopenic purpura, while the incidence of acute, persistent, and chronic immune thrombocytopenic purpura were 38.9%, 24.1%, and 37%, respectively. Besides, the whole population was at risk of having immune thrombocytopenic purpura; thus, the incidence was 4.96 per 100,000 persons at risk. Additionally, the association of immune thrombocytopenic purpura types was significant with age (p<0.001), in which acute immune thrombocytopenic purpura was more in pediatrics, and chronic was more in adults. Furthermore, the association of bone marrow megakaryocytes was significant with peripheral platelets, bone marrow megakaryocytes increased by decreasing peripheral platelets.
Keywords: Autoimmune disease Bone marrow aspiration Retrospective observational studySulaimaniyah